Hak Istri Menolak Rujuk Perspektif Islam dan Gender - Arini Rufaida (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2019)
Abstract: Studying the problems of women in various fields, especially marriage, always faces its own challenges. The lack of wife's rights in marriage gets some contradictions from a gender perspective. Did not rule out the possibility of connection with the wife's right to refuse reconciliation. This paper synergizes Islamic and gender perspectives on the issue of wife's right to refuse reconciliation. Efforts are being made to identify the shifts related to the classical fiqh formulation into a more egalitarian formulation according to the guidance of modern times. In addition, the next effort is to identify a new business of reasoning from the abstract domain to concrete rules. There are two steps that can be done, namely by analyzing the problem using the theory of equality and gender justice and the theory of maslahah from the perspective of several competent figures in their fields. From this, this paper confirms the similarity of perception between the aims of Islamic teachings (maqasid ash-shari’ah) and gender equality and human rights, that is the right for anyone to consider everything that will be done as long as it brings benefit.